Propionic acid production from soy molasses by Propionibacterium acidipropionici: Fermentation kinetics and economic analysis. (February 2018) - Yang, Hopen; Wang, Zhongqiang; Lin, Meng; Yang, Shang-Tian
Highlights: Soy molasses (SM) is a byproduct containing soy oligosaccharides difficult to digest. Propionic acid (PA) production from untreated SM by P. acidipropionici was studied. PA productivity >0.8 g/L h and yield of 0.42 g/g were obtained from SM. The process compares favorably with glucose or other biomass feedstocks in cost. This offers an economical process for production of food-grade calcium propionate. Abstract: Propionic acid (PA) is a specialty chemical; its calcium salt is widely used as food preservative. Soy molasses (SM), a low-value byproduct from soybean refinery, contains sucrose and raffinose-family oligosaccharides (RFO), which are difficult to digest for most animals and industrial microorganisms. The feasibility of using SM for PA production by P. acidipropionici, which has genes encoding enzymes necessary for RFO hydrolysis, was studied. With corn steep liquor as the nitrogen source, stable long-term PA production from SM was demonstrated in sequential batch fermentations, achieving PA productivity of >0.8 g/L h and yield of 0.42 g/g sugar at pH 6.5. Economic analysis showed that calcium propionate as the main component (63.5%) in the product could be produced at US $1.55/kg for a 3000-MT plant with a capital investment of US $10.82 million. At $3.0/kg for the product, the process offers attractive 40% return of investment and is promising for commercial application.